(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2024)
The work opens with a broad portico, entitled 500 years later: loves and dislikes between brothers, pointing out that the visceral anti-colonialism with and disaffection between brothers, pointing out that the visceral anticolonialism with the collapse of statues of colonizers. The structure of the book is as follows: At Part I, presents the results by country of the different topics covered, as well as the facts and characters the most important facts and personalities of their country, racism and prejudice towards the different and prejudice against those who are different, negative and positive images of the colonization of the colonization of America, trust in institutions, the most important problems, values and counter-values, and the values and counter-values of machismo, sexism, sexual morality, religiosity and level of happiness, religiosity and level of happiness. The following parts present the variations of gender, age, level of variations in gender, age, level of education, religiosity and political options, the comparative comparison from the 1993 survey to 2019, analyzing the profound changes.